A New Technology for Efficient, High Yield Carbon Dioxide and Water Transformation to Methane by Electrolysis in Molten Salts. Issue 6 (14th July 2016) - Wu, Hongjun; Ji, Deqiang; Li, Lili; Yuan, Dandan; Zhu, Yanji; Wang, Baohui; Zhang, Zhonghai; Licht, Stuart
Abstract : This study presents a new green technology for the sustainable utilization of carbon dioxide. Synthetic methane, if produced efficiently and with low carbon footprint, provides a ready replacement for natural gas in the existing energy, manufacturing, and transportation industries. The first technology for the production of methane from CO2 and water by molten electrolysis is demonstrated. The technology is more efficient than alternative renewable methane production by microbial, aqueous, or solid oxide electrolysis, or than various photocatalytic processes. Methane is produced at 1000‐fold the rate observed in photoelectrochemical systems, and without noble metals or an external hydrogen source. Added steam and CO2 continuously renew the electrolyte. CO2 and H2 O are directly transformed by electrolysis at 97.4% current efficiency at a constant current of 250 mA through 20 cm 2 iron and nickel electrodes in a 600 °C alkali carbonate/LiOH electrolyte at low (<2 V) energy. The electrolysis product is comprised of 64.9% methane, 34.8% H2, and 0.3% longer (than C1) hydrocarbons. Abstract : The first high yield, low energy synthesis of methane synthesis accomplished by (solar or other renewable powered) electrolysis in molten salts from carbon dioxide and water to mitigate the consequences of climate change is presented. The production of methane is at a high rate, and the synthesis requires only an electrocatalytic iron cathode, a nickel anode, and alkali salts.